2019
DOI: 10.1016/j.ijhydene.2019.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Multi-component high aspect ratio turbulent jets issuing from non-planar nozzles

Abstract: Fundamental insight into the physics of buoyant gas dispersion from realistic flow geometries is necessary to accurately predict flow structures associated with hydrogen outflow from accidental leaks and the associated flammability envelope. Using helium as an experimental proxy, turbulent buoyant jets issuing from high-aspect-ratio slots on the side wall of a circular tube were studied experimentally applying simultaneous particle image velocimetry (PIV) and planar laser-induced fluorescence (PLIF) techniques… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The slot is no longer a conventional flat leakage gap but a curved leakage gap similar to the actual pipeline. In this case, the jet in the pipeline crack will be deflected along the central axis of the jet, and an increase in the aspect ratio will result in a decrease in the deflection angle and axial concentration attenuation rate. , The characterization of subsonic jets in fuel cells involves multiple scales, ranging from the microscopic scale of the leakage gap to the macroscopic scale of the environmental domain. Therefore, numerical simulation studies need to develop multiscale modeling techniques to better capture the details and global behavior of the jet.…”
Section: Hydrogen Jetmentioning
confidence: 99%
“…The slot is no longer a conventional flat leakage gap but a curved leakage gap similar to the actual pipeline. In this case, the jet in the pipeline crack will be deflected along the central axis of the jet, and an increase in the aspect ratio will result in a decrease in the deflection angle and axial concentration attenuation rate. , The characterization of subsonic jets in fuel cells involves multiple scales, ranging from the microscopic scale of the leakage gap to the macroscopic scale of the environmental domain. Therefore, numerical simulation studies need to develop multiscale modeling techniques to better capture the details and global behavior of the jet.…”
Section: Hydrogen Jetmentioning
confidence: 99%
“…The third case, the accidental leak jets generating from a fracture in the wall of a pipeline (as a leak from a fracture in a pipeline can be considered as a leak from an orifice, van Zyl, 2014 [9]), has received a particular attention during the last years. In fact, the new scenarios related to the availability and cost of water, oil and gas and of their transportation have forced to pay more attention to the efficiency of the distribution systems and, in particular, to the leakage control and detection (Soleimani nia et al, 2019 [10], Ferrante et al, 2013) [11]). Moreover, a high-pressure non-controlled jet can be dangerous for the safety of people working or living in the vicinity of industrial plants and pipelines (Mohsin et al, 2015 [12]).…”
Section: Introductionmentioning
confidence: 99%
“…Other Authors investigated the jet behaviour outside the pipe of reacting or flammable fluids, such as the release of hydrogen or helium into the air, with the buoyancy (i.e. the difference in density) and the chemical reactions playing a relevant role in the behaviour of the jet (Soleimani nia et al, 2018 [15] and 2019 [10]). Anyway, they concluded that the conventional round jet assumptions are not adequate to predict the behavior of turbulent buoyant jets issuing from a slot on the lateral wall of a pipe, in particular regarding the direction and axisymmetry of the jets.…”
Section: Introductionmentioning
confidence: 99%